NARASI ANTI-IMIGRAN DALAM KRISIS PENGUNGSI EROPA TAHUN 2015 SEBAGAI REFLEKSI ATAS KRISIS IDENTITAS EROPA - Muhammad Iqbal Yunazwardi (UNIDA Gontor, 2021)
The Refugee Crisis in 2015 has considered creating a major problem to European society. This issue was capitalized by far-right political movement to create anti-immigrant narratives. Right-wing political groups have linked the anti-immigrant narratives to the negative impact European societies have had on security, politics, economics and social culture. In this article, the author argues that the increase of anti-immigrant narratives also entails a crucial aspect that is important to analyze, which is the fragile construction of the European identity. The integration of European identity, multiculturalism, and social cohesion are the important aspects of such identity. This is more apparent nowadays as the immigrant population is increasing. The author suggests two points of view on this ma er: the discussion on migrants in Europe and how the anti-immigrant narrative dominates the transition discourse contestation in Europe, especially how the narratives develop after the 2015 refugee crisis.